(untitled) (Research, Society and Development, 2022)
Distillation is an important unit operation in several industrial processes. It is used to purify and separate various compounds, and it is based on the difference in volatility between the components present in the operation. The objective of the present work was to build a distillation column of removable perforated stages for laboratory practices of students at the Universidade Federal do Triângulo Mineiro, which also allows to study the effects of some variables: number of stages, reflux, feeding condition, thermal load employed and compositions in the output currents. For such analyses, the thermodynamic models used were validated through experimental and simulated data. The simulations were performed using the free software COFE®, ChemSep® and Excel®. The parameters were evaluated taking into account the exit of nearly pure water at the bottom of the column and an overhead stream of anhydrous ethanol leaving the column. Adaptations in order to optimize both the available structure and equipment operation as well as the results are the purposes of this work.